FAKTOR-FAKTOR YANG MEMPENGARUHI FUNGSI KOGNITIF PADA PASIEN DIABETES MELITUS TIPE 2 - Yaumi Faiza; Yuliarni Syafrita (HUMAN CARE JOURNAL, 2020)
Background :The number of Dementia is increasing year by year, and it will be 3.980.000 in 2050 In Indonesia, as well as the world. Dementia can be triggered by Diabetes Mellitus type 2. Long hyperglycemia can induce beta amiloid in brain, that declines the cognitive function. Besides, some factors can influence cognitive function such as age, sex, level of education and duration of DM type 2. The aim of this study is to review the faktors that influence cognitive function of DM type 2.Methods: The study design was cross sectional, with 56 subjects.  The collective data were age, sex, level of education, duration of DM type 2,  and cognitive function which is determined by using MoCA Ina The variables associated were tested by using Chi-Square Test, and the association is significant if p<0,05.Results: From 56 research subjects,32 (57,14%) subjects are female,, high level of education is 76,79 %, and 57,14 % subjects are suffering from DM for 5-<10 years. The average MoCA Ina value was 23 + 3.47. There are 37 (66.1 %) subjects with cognitive decline. There is no significant associations between age, sex,level of education, duration of DM and cognitive function (p>0,05).